2008
DOI: 10.1161/circresaha.107.163188
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Pitx2 Differentially Regulates the Left Atrial Identity and Ventricular Asymmetric Remodeling Programs

Abstract: Abstract-The Pitx2 gene regulates left-right (L/R) asymmetrical cardiac morphogenesis. Constitutive Pitx2 knock out (ko) mice die before birth and display, among other defects, right atrial isomerism, atrial and ventricular septal defects, and double outlet right ventricle. The myocardial role of the gene has not been dissected. In particular, how Pitx2 regulates the differential L/R cardiac identity program is not clear. Additionally, the relation between Pitx2 ko ventricular defects and the gene expression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
84
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 38 publications
8
84
0
Order By: Relevance
“…Overall, these findings indicate that during the developmental window comprising interventricular septum formation (E11.5-E15.5) (Miquerol et al, 2012) PITX2B positive cells displayed a dynamic distribution within this ventricular compartment. At E13.5, we found that a major proportion of PITX2B ventricular positive nuclei are located in the interventricular septum and these cells shift to minimal PITX2B expression at E15.5 when ventricular septation is fully completed (Miquerol et al, 2012).In addition, and based on recent reports that pointed out a possible participation of PITX2 in the development of atrioventricular (AV) canal (Tessari et al, 2008), we investigated whether PITX2B could be involved in AV canal formation by analysing the number of PITX2B positive cells in those structures. At stages E9.5 and E11.5 the proportion of PITX2B positive mesenchymal cells in AV cushions is clearly low, around 4% (Fig.…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…Overall, these findings indicate that during the developmental window comprising interventricular septum formation (E11.5-E15.5) (Miquerol et al, 2012) PITX2B positive cells displayed a dynamic distribution within this ventricular compartment. At E13.5, we found that a major proportion of PITX2B ventricular positive nuclei are located in the interventricular septum and these cells shift to minimal PITX2B expression at E15.5 when ventricular septation is fully completed (Miquerol et al, 2012).In addition, and based on recent reports that pointed out a possible participation of PITX2 in the development of atrioventricular (AV) canal (Tessari et al, 2008), we investigated whether PITX2B could be involved in AV canal formation by analysing the number of PITX2B positive cells in those structures. At stages E9.5 and E11.5 the proportion of PITX2B positive mesenchymal cells in AV cushions is clearly low, around 4% (Fig.…”
mentioning
confidence: 61%
“…In addition, we cannot rule out the possibility that different PITX2 isoforms could be coexpressed in the same cardiac cells, according to the fact that different isoforms of PITX2 can act together forming homo and heterodimers leading to transcriptional synergism (Cox et al, 2002;Saadi et al, 2003). Current studies suggest that Pitx2-mediated signalling during cardiogenesis is conducted within three different cell types: the myocardium, the cardiac neural crest (CNC) cells, and the pharyngeal arch mesenchyme (Campione et al, 1999;Chinchilla et al, 2011; Franco et al, 2003;Kioussi et al, 2002;Liu et al, 2002;Tessari et al, 2008), minimizing the possible role that Pitx2 a, b or c, may have during development of epicardial and endocardial derivatives. In addition, it was previously reported only that Pitx2c expression is never detected in endocardium (Liu et al, 2002).…”
Section: (A-d) Nuclear and Cytoplasm Immunohistochemical Stain Obtainmentioning
confidence: 99%
See 2 more Smart Citations
“…Asymmetric distributions of secreted factors and asymmetric expression of transcription factors guide the asymmetric development of the organs in digestive, circulatory and respiratory systems. Nodal is one of these asymmetrically distributed secreted factors and Pitx2 is one of these asymmetrically expressed transcription factors (10,11). Some studies have demonstrated that human orthologue of the Nodal signaling genes, ACVR2B (12), LEFTYA (13) and CFC1 (14), were mutated in patients with heterotaxia.…”
Section: Introductionmentioning
confidence: 99%